2006
DOI: 10.1007/s10495-005-3275-z
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in prostate tumor PC-3 cells and inhibition of xenograft prostate tumor growth by the vanilloid capsaicin

Abstract: Capsaicin, the pungent ingredient of hot chilli pepper, has been recently shown to induce apoptosis in several cell lines through a not well known mechanism. Here, we investigated the role of the vanilloid capsaicin in the death regulation of the human cancer androgen-resistant cell line PC-3. Capsaicin inhibited the growth of PC-3 with an IC(50) of 20 microM cells and induced cell apoptosis, as assessed by flow cytometry and nuclei staining with DAPI. Capsaicin induced apoptosis in prostate cells by a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
136
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 25 publications
8
136
1
6
Order By: Relevance
“…The absence of TRPV1 in the P2 pancreas suggests that neonatal capsaicin could not affect pancreatic cells via a receptor-specific mechanism. However, as noted by Diaz-Laviada and Rodriguez-Henche (41), for many tumor cell lines, capsaicin effects, especially with respect to alterations in apoptosis or proliferation, are TRPV1 independent (33,42,43). We therefore examined pancreata from P2 vehicle-and capsaicintreated mice stained for markers of apoptosis (anticaspase 3) and proliferation (anti-Ki67) 2 h posttreatment.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The absence of TRPV1 in the P2 pancreas suggests that neonatal capsaicin could not affect pancreatic cells via a receptor-specific mechanism. However, as noted by Diaz-Laviada and Rodriguez-Henche (41), for many tumor cell lines, capsaicin effects, especially with respect to alterations in apoptosis or proliferation, are TRPV1 independent (33,42,43). We therefore examined pancreata from P2 vehicle-and capsaicintreated mice stained for markers of apoptosis (anticaspase 3) and proliferation (anti-Ki67) 2 h posttreatment.…”
Section: Resultsmentioning
confidence: 97%
“…To examine how sensory neurons impact PDAC initiation and progression, we first determined if neonatal capsaicin had direct effects on pancreatic cells because previous studies using cancer-derived cell lines showed it affected apoptosis and proliferation (28)(29)(30)(31)(32)(33)(34). The neurotoxic effects of neonatal capsaicin treatment are assumed to be via binding to TRPV1, the vanilloid receptor specific for capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…The association between capsaicin and carcinogenesis has long been investigated, which, however, reached paradoxical observations in different tumor types. It is reported that capsaicin displayed an anti-proliferative activity against lung cancer [5], prostate cancer [6] and pancreatic cancer [7]; nevertheless, capsaicin also acts as a co-carcinogen in the development of skin cancer [8]. Further, it is reported that capsaicin induced apoptosis in human breast cancer cell line through caspase-independent pathway [9].…”
mentioning
confidence: 99%
“…1 Tumour growth of the PC-3 cells was reduced by 40% when capsaicin was administered to mice 4 weeks after tumour inoculation. 2 We report PSA stabilization on capsaicin in a patient with PSA relapse after radiotherapy for a T2b, Gleason score 7 adenocarcinoma of the prostate. At biochemical failure, the patient did not tolerate androgen ablation therapy and started taking habanero sauce containing capsaicin 2.5 to 5 mL daily in April 2006.…”
Section: Discussionmentioning
confidence: 84%
“…1 Capsaicin was also shown to induce apoptosis via reactive oxygen species (ROS) formation, dissipation of mitochondrial inner transmembrane potential and caspase 3 activation in PC-3 cells. 2 Further studies have shown that ROS generation may be necessary for ceramide accumulation and cell growth inhibition by capsaicin. 3 Pathways involving Jun N-terminal Kinase (JNK) and extracellular signal-regulated kinase (ERK) cascades have also been implicated in anti-proliferative effects of capsaicin.…”
Section: Discussionmentioning
confidence: 99%